(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Herpes simplex keratitis (HSK) is a severe ophthalmic pathology which comprises 20-50% of inflammatory diseases in the cornea. Since keratitis is characterized by a long-term duration, severity, and a tendency to recurrence, studies on ophthalmic herpes and searches for new treatments are of great relevance. Our clinical case demonstrated successful combined treatment of a recurrent stromal herpetic corneal lesion with ulceration. Both treatments, conservative (complex etiotropic, anti-viral, anti-inflammatory, and nutrition-improving) and surgical (an onlay technique), were successful. At 12 months after surgery, the patients had no pain syndrome; the corneal surface was epithelialized. No recurrence of herpetic keratitis was observed. Thus, a combination of etiotropic pathogenic treatment and AM transplantation appears to be effective for severe long-lasting recurrent herpetic keratitis with the presence of defects on the corneal surface.